Green Transformational Leadership, Green Creativity, and Green Product Development Performance Moderated by Green Dynamic Capabilities - Jerry Owusu Banahene; Divina Dzifa Classpeters; Oscar Agyemang Opoku (iRASD Journal of Management)
This research paper investigates how the relationship between Green Transformation Leadership (GTL), Green Creativity (GC), and Green Product Development (GPD) performance is moderated by Green Dynamic Capabilities (GDC). The research used a quantitative methodology and questionnaires to gather data, and it was based on the natural resource-based view of the firm. This study sampled 166 private manufacturing companies in Ghana. Structural Equation Modeling was used to analyse the data with the aid of Amos and SPSS software. The empirical findings from the study shows that the performance of green product creation and GTL are mediated by GDC. The study also showed that GTL affects the efficiency of GPD through green innovation. Additionally, it was found that GDC, via GC, regulates the association between GTL and green product creation. The study's results advance our understanding of how GDC mediate the link between GTL and GPD in firms.